Advances and trends in structural engineering, mechanics, and computation : proceedings of the Fourth International Conference on Structural Enginering, Mechanics and Computation, 6-8 September 2010, Cape Town, South Africa /: proceedings of the Fourth International Conference on Structural Enginering, Mechanics and Computation, 6-8 September 2010, Cape Town, South Africa. (©2010) - Unknown
No abstract available